An overview of new biomolecular pathways in pathogen-related cancers. (June 2015) - Tornesello, Maria Lina; Buonaguro, Luigi; Buonaguro, Franco M
ABSTRACT : Cancer molecular pathways are combinations of metabolic processes deregulated in neoplastic cells. Besides pathways specific to tissues from which cancers originate, common neoplastic traits are present among most tumors. Hanahan and Weinberg have described the most critical 'hallmarks' shared by many cancer types. In recent years, cancer stem cell specific properties and pathways have also been identified. Other altered pathways are peculiar of cancer type and cancer stage, even in different cancer stem cell types. In pathogen-related tumors, the alteration of inflammatory and immunologic response along with impairment of cell cycle control represents key molecular events of tumor progression. This article summarizes the recent discoveries of new altered pathways in cancer and their importance in cancer diagnosis and tailored therapies.